Perception of the elderly undergoing hemodialysis treatment (Research, Society and Development, 2021)
As the population ages, the number of non-communicable chronic diseases increases, including chronic renal failure, which in the terminal phase leads the patient to undergo renal replacement therapy, one of the methods is in the form of hemodialysis, a treatment that keeps life, however, it requires the patient to live with the restrictions imposed by health and treatment conditions. The objective of this work is to recognize the main difficulties experienced by the elderly undergoing hemodialysis treatment in the municipality of Cáceres-MT. This is a descriptive, exploratory study with a qualitative approach, carried out with 16 elderly people, between the months of August and November 2020. For the interview, a semi-structured questionnaire containing open questions was used. Among the elderly interviewed, 50% were male and 50% female, with an age ranging from 60 to 81 years. After analyzing the interviews, we obtained three categories: perceptions and experiences about the impact of the disease and the process of acceptance of hemodialysis treatment; the elderly undergoing hemodialysis treatment: main difficulties experienced; and faith, family and multiprofessional team: coping with the disease and supporting adherence to treatment. This study revealed that the elderly on hemodialysis live with several limitations and difficulties, needing the full support of family members, society, especially the nursing team, helping them to solve the difficulties encountered, knowing how to listen to them and understanding them in their individuality and magnitude, creating educational actions to promote a better quality of life so that despite the limitations these elderly people can live better.